Effect of high strain rate and low temperature on mode II fracture toughness of ductile adhesive. (November 2018) - Jia, Zhemin; Yuan, Guoqing; Hui, David; Feng, Xiaoping; Zou, Yun
Abstract: Adhesive joints have a great potential use in different industrial applications which may encounter low temperature and high strain rate conditions, the fracture behavior of adhesive needs to be reliably predicted under such conditions. This paper experimentally studies the mode II fracture toughness of a polyurethane (PU) adhesive at room temperature (RT) under quasi-static condition with J-integral method and at low temperatures under high strain rate conditions with compliance-based beam method (CBBM), which does not need the observation of crack propagation. Typical R-curves of the PU ductile adhesive under the loading rate of 2 m/s, 3 m/s and at RT, −20°C, −40°C respectively are obtained. From the experimental results, low temperature and high strain rate has great effect on mode II fracture toughness of adhesive. The mode II fracture toughness of this PU adhesive decreases by at least one order of magnitude when conditions vary from quasi-static to high rate. Under the high strain rate conditions, the mode II fracture toughness of adhesive increases with the decrease of the temperature. At −40°C under the loading rate of 3 m/s, mode II fracture toughness of adhesive increases by 130% compared with the data at RT under the loading speed of 2 m/s. Through the experiment, the relationship between the mode II fracture toughness of adhesive, the nominal shear strain rate and the temperature is obtained. It is concluded that the mode II fracture toughness of adhesive at RT under quasi-static condition cannot be used to design and analyze adhesive joints at low temperatures under high strain rate conditions.